ROLE OF FINTECH AS A BUSINESS INNOVATION ECOSYSTEM- AN EMPIRICAL STUDY - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana (The journal of contemporary issues in business and government, 2022)
This paper analyses the advent of Fintech in the established ecosystem of businesses. There are ongoing innovations in the business environment, and Fintech has played a significant role in it. The fusion of digital technology and financial services has given rise to a concept called Fintech (Agarwal & Zhang, 2020). The ecosystem consisting of businesses flourishing in innovation is seen to adapt to Fintech to get a competitive advantage over other firms. The length and breadth of companies are rapidly widening with the emergence of Fintech. It gives rise to a centrally managed organization that has replaced the hierarchal system and turned into a fresh model. The disruption created by Fintech has helped many businesses to flourish by facilitating an innovative business ecosystem within their premises. There is little work associated with the role of Fintech in the ecosystem of businesses in evolution and development concerning pathbreaking innovative solutions. This study has tried to capture the essential aspects of Fintech and its application in several businesses and its innovative environment (Lee & Shin, 2018). It clarifies that the research about disruptive innovations and the creative environment in businesses is the need of the hour and deserves more attention than the present scenario. A sample of 189 people working in different financial sectors was surveyed to know the different roles and significance of Fintech as a Business Innovation Ecosystem in the financial sector. "Mean and t-test" was applied to analyze the data and results. It is found that Fintech is playing a significant part as a Business Innovation Ecosystem in the financial sector.